2017
DOI: 10.1262/jrd.2016-160
|View full text |Cite
|
Sign up to set email alerts
|

Differentially methylated CpG sites in bull spermatozoa revealed by human DNA methylation arrays and bisulfite analysis

Abstract: The methylation status of sperm DNA differs between individual bulls. However, the relationship between methylation status and bull sperm parameters is not well elucidated. The present study investigated genome-wide methylation profiles at 450,000 CpG sites in bull spermatozoa by using a human DNA methylation microarray. Semen samples from three adult Japanese Black bulls with different in vitro fertilization (IVF) results and from a young Holstein bull through sexual maturation (at ages 10, 10.5, 15, and 25 m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
24
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(24 citation statements)
references
References 27 publications
0
24
0
Order By: Relevance
“…Moreover, some of these DMR were mapped to genes that are transcriptionally active during preimplantation stages, suggesting their potential role in early embryo development ( Fang et al, 2019 ). Similarly, age-related DMRs were observed in bovine spermatozoa ( Takeda et al, 2017 , 2019 ; Lambert et al, 2018 ), and 57 of 2223 DMRs (2.56%) were retained in blastocysts ( Lambert et al, 2018 ; Wu et al, 2020 ). Among the genes that are mapped with these DMRs, some of them were involved in spermatogenesis (FKBP6) and embryonic preimplantation development (AKT2).…”
Section: The Known Non-genetic Parental Influences In Dairy Cattlementioning
confidence: 82%
“…Moreover, some of these DMR were mapped to genes that are transcriptionally active during preimplantation stages, suggesting their potential role in early embryo development ( Fang et al, 2019 ). Similarly, age-related DMRs were observed in bovine spermatozoa ( Takeda et al, 2017 , 2019 ; Lambert et al, 2018 ), and 57 of 2223 DMRs (2.56%) were retained in blastocysts ( Lambert et al, 2018 ; Wu et al, 2020 ). Among the genes that are mapped with these DMRs, some of them were involved in spermatogenesis (FKBP6) and embryonic preimplantation development (AKT2).…”
Section: The Known Non-genetic Parental Influences In Dairy Cattlementioning
confidence: 82%
“…Recently, a study showed that an increased expression of miR‐29b was associated with a decrease in DNMT 1 in adult rats, resulting in apoptosis and an elevated risk of infertility (Meunier et al, ). DNA methylation is an epigenetic control of gene expression in male fertility (Takeda et al, ), and DNA methyltransferases mediate the DNA methylation process by transferring a methyl group to genomic DNA sequence. In this study, the relative levels of DNMT1 were higher in spermatozoa from HF sires compared to those from LH bulls suggesting that spermatozoa of HF bulls maintain proper DNA methylation (Zhou et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…In the mouse, sperm cells from elderly fathers display DNA methylation signatures of age in genes relevant to senescence, some of which are transmitted to the offspring and potentially contribute to their shorter lifespan and exacerbate aging-associated pathologies (Xie et al 2018). In the dairy industry, the use of semen collected from very young bulls enables both reduced rearing costs and increased genetic gain, but this practice is not without significance because intra-individual variations affecting DNA methylation in semen collected at different ages have recently been reported (Takeda et al 2017(Takeda et al , 2019Lambert et al 2018). In the earlier study (Takeda et al 2017), semen samples displaying contrasted quality parameters, and IVF Note: CR, conception rate; SQ, semen quality; IVF, in vitro fertilization; CPF, chlorpyrifos; PCR, polymerase chain reaction.…”
Section: Inter-and Intra-individual Variations In the Sperm Dna Methymentioning
confidence: 99%